Inclusive Arts Education: A Systematised Review - Escaño, Carlos; Hernández-Domínguez, María Cristina; Correa-Moreno, José Manuel; Castro-León, Elke (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2025)
This article develops a systematised review of scientific literature with the aim of drawing a current map of the relationship between the conceptual fields of arts education and inclusion. A prescriptive approach to be able to develop further research and educational activities that contemplate this interdisciplinary framework as a territory of action, whether they are online contexts or spaces outside the digital territory. The work is part of the project ‘Inclusive Online Arts Education: development and evaluation of a comprehensive MOOC model for teacher training (EDARCLUSION)’ (PID2021-127124OB-I00). The systematised review is an approach that involves principles of systematic review, but with greater flexibility in its implementation. The research exercise is approached using the SALSA (Search, Appraisal, Synthesis, Analysis) Framework, enabling a clear and contrasted structure. The Scopus and Web of Science databases have provided the search territory for the studies, finally concluding in a set of 83 scientific articles. The results underline the relevance of the idea and praxis of inclusion and accessibility within arts education.  At the same time, they show the relevance of approaching Arts Education through innovative and critical pedagogical approaches and methodologies.
Keywords: Arts Education; Inclusion; Systematised Review; SALSA Approach; Innovative Methodologies